Positivity Conditions for Operators with Difference Kernels in Reflexive Spaces - Askhabov, S. N. (Journal of mathematical sciences (New York, N.Y.), 2020)
Using methods of the theory of discrete and intFourier transforms, we obtain necessary and sufficient conditions for of the positivity of linear discrete, integral, and integro-differential operators with difference kernels in the spaces ℓ p and L p for 1 < p < ∞ and present examples illustrating the results obtained.